Antibacterial intraosseous implant surface coating that responds to changes in the bacterial microenvironment - Bai, Xin; Yu, Jiawei; Xiao, Jie; Wang, Yanping; Li, Zhe; Wang, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
The bone implant-associated infection has long become one of the most challenging problems faced by orthopedic surgeons. Drug-loaded antibacterial coating on the surface of metal implant has of late become a popular research area. However, much antibacterial coating was difficult to locally stably release the effective dose of the drug. In the present study, the thickness and contact angle measurement of the multilayer confirmed successful assembly of multi-lamellar membrane structures. The measurement the zone of bacterial inhibition could can support the (MMT/HA-RFP)10 multilayer films structure gradually degraded and exhibited great concentration-dependent degradation traits following incubation with HAS solution and Staphylococcus aureus. The in vivo results were similar to those obtained in vitro, all data provided further evidence for the (MMT/HA-RFP)10 multilayer films structure has good antibacterial properties and excellent biocompatibility. We concluded that the prepared anti-infective coating in this experiment give the possibility of further research into possible use in clinic work.